Synthese Bibliographique Sur Les Technologies De Maitrise De L’eau Pour Les Cultures Dans Les Zones Humides Tropicales - Sohou, Laurenda Rose; Kénou, Christel; Sogbedji, Jean Mianikpo; Sintondji, Luc Ollivier; Agbossou, Euloge Kossi; Mensah, Guy Apollinaire (European Scientific Journal, ESJ, 2017)
Water management for agriculture is a worry in the world. The objective of this study is to provide an overview of the current knowledge on water control’s technologies for the crops in wetlands. Comparison research work carried out on different irrigation systems revealed that drip irrigation can lead to 28-35% of water saving in relation to irrigation surface technic. Surface irrigation offers higher yield in relation to drip irrigation. It’s necessary to improve knowledge and local communities’ technics on different water control technologies in order to provide irrigation’s functions in developing countries. Research efforts on three important concepts are necessary such as : (i) local communities perceptions on crops water need and the responses of differents crops technologies on crops yield ; (ii) interactions between agricultures prospects, water controls innvations and economics benefits of theses technologies.